Research overview of Osmanthus fragrans beer - Zhang, Zenghao; Cui, Yunqian; Fu, Yiting; Yin, Zemiao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Osmanthus fragranced flowers, rich in a variety of beneficial components, is a good example of homology of medicine and food. Brewing beer with Osmanthus fragrans is not only enjoyable but also has health benefits. The article introduces the beneficial components and aromatic substances of Osmanthus fragrans, discusses the Osmanthus fragrans beer brewing process and the characteristic flavor components, in order to provide theoretical support and technical reference for the research and development of Osmanthus fragrans beer.